THE MODEL FOR THE DEVELOPMENT OF THE THALABAH CHARACTER IN THE DAYAH SALAFIYAH IN THE REGENCY OF UTARA ACEH ACEH PROVINCE - Akhyar, Syaiful; Mukti, Abd; Fauzan, Fauzan (Universitas Dharmawangsa Medan, 2021)
The moral development material for the Salafiyah dayah in North Aceh Regency is in the form of turats (bald books) written by various scholars from the Ahlussunnah wal Jamaah circles, starting from Tambih al-Ghafilin, Taisir al-Khalaq, Ta'lim al-Muta' scholars, Muraqi al-Ubudiyyah, Siraj al-Thalibin, Syarah al-Hikam and Ihya Ulum al-Din. The content of moral development material includes: 1) Morals towards Allah swt., in carrying out monotheism, worship, and reading the Koran. 2) Morals with fellow humans which include morals towards both parents, teachers, fellow students and the opposite sex. 3) Morals with the environment which includes morals towards animals and plants.Keywords: Moral of Thalabah, Dayah Salafiyah